Partisipasi Masyarakat Dalam Pelaksanaan Program Kotaku (Kota Tanpa Kumuh) Pada Kawasan Permukiman Kumuh di Kelurahan Pasar Pandan Air Mati Kecamatan Tanjung Harapan Kota Solok - ramza nuari delyus; Dian Kurnia Anggreta; Sri Rahmadani (Universitas Muhammadiyah Sumatera Utara, 2023)
This study examines community participation in the Kotaku Program (Slum Alleviation), one of the government's programs aimed at addressing slum settlement issues in urban areas. This research aims to examine community participation at the micro-level, within the field of Sociology. The theory used in this research is the theory of social exchange from George C. Homans' perspective. This research employs a qualitative research method, specifically a case study. There were 10 informants in the research, consisting of city government officials, local government representatives, facilitators, and community members participating in the Kotaku program. Data analysis techniques in the research were carried out through data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that community participation in the implementation of the Kotaku program is demonstrated by allocating time for involvement, material contributions, and labor in the construction of facilities such as green spaces, drainage systems, and waste disposal areas. Based on the exchange theory, participating communities receive rewards in the form of improved infrastructure and a betterquality environment. This research is able to explain the reasons for local community participation but has not yet assessed the level of participation. Therefore, further research is needed to measure the level of participation. Keywords: Community Participation, Kotaku Program, Slum Alleviation, Social exchange.